The role of temporal lobectomy as a part of surgical resuscitation in patients with severe traumatic brain injury - Hakan, A; Daltaban, Iskender; Vural, Sevilay (Asian Journal of Neurosurgery, 2019)
Background: Traumatic brain injuries (TBIs) are serious morbidity and mortality risk for especially in the young population. Primary and secondary injury mechanisms may cause cerebral edema and intracranial hypertension. The target point of the TBI treatment is lowering the intracranial pressure medically or surgically if indicated. Methods: The files of the patients with severe brain injury admitted between January 2015 and December 2017 were reviewed retrospectively. Patients who underwent decompression surgery due to severe brain injury ([The Glasgow Coma Scale [GCS] score] <8) and additional temporal lobectomy were included in the study group. Results: Ten patients were included in the study during the 3 years. All the patients were suffering from blunt severe TBI. Traumatic etiology was vehicle traffic accident in six cases, nonvehicle traffic accident in two cases, and falling from height in two cases. All the cases suffered from blunt trauma. The admission GCS of the patients was 4–7 (mean = 5.5). Right-sided decompression surgery and lobectomy were performed for seven patients and left-sided in three cases. The postoperational survival was 60%. All the survivors were functionally independent with mild cognitive disturbances. Conclusion: Temporal lobectomy might be added to the surgery to apply all the interventions available in combat with progressively increasing intracerebral pressure as a part of surgical resuscitation.
Keywords: Decompressive craniectomy; neurosurgical resuscitation; severe traumatic brain injury; temporal lobectomy